Active Physics Learning: Making Possible Students' Cognitive Growth, Positive Emotions and Amazing Creativity - Josip Sliško (Karolinum Press, 2017)
It is now well known that carefully designed sequences of active physics learning support students' comprehension of physical concepts and laws. If only this were its eﬀect, active learning should replace lecture-based teaching and passive students' learning at all educational levels. Fortunately, the impacts of active learning experiences in students are much broader. In this paper I present a few examples of tasks that are suited for engaging students in active learning along with research-based and anecdotal evidence about eﬀects of active physics learning on students' cognitive level, emotions and creativity.